Pengaruh Gaya Kognitif dan Motivasi Belajar Matematika Terhadap Kemampuan Pemecahan Masalah Matematika Mahasiswa PGSD - Patta, Rahmawati; jafar, muhammad idris; S, Syamsuddin (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2019)
This study aims to determine the effect of cognitive style and motivation to learn mathematics on the ability to solve mathematical problems. The research method used is ecso facto research by using the Geft test instrument to measure cognitive style, a learning motivation scale questionnaire and a test of mathematical problem solving abilities. The population in this study was PGSD Bone Campus VI FIP UNM students who programed an introductory course on basic mathematics. The data analysis technique used is Two-Way Anova. The results showed that (a) cognitive style significantly influenced the ability of mathematical problem solving, (b) the motivation to learn mathematics had a significant positive effect on the ability to solve mathematical problems, (c) the cognitive style and mathematics learning motivation together significantly influenced on the ability to solve mathematical problems, (d) there are differences in the ability to solve mathematical problems based on cognitive style and learning motivation where the independent field skills with high mathematical learning motivation results in the ability to solve mathematical problems in the good category. Conclusion cognitive style and motivation to learn mathematics have a significant influence on the ability to solve mathematical problems.